Faktor-faktor yang berhubungan dengan latihan Range Of Motion (ROM) terhadap peningkatan kemampuan ROM pada pasien post stroke Hemipareses di Ruang Fisioterapi RS. Islam Cempaka Putih Jakarta - Naziyah Taufik Djafar; Yarni (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2020)
Stroke according to the World Health Organization (WHO) are clinical signs that develop rapidly due to impaired focal brain function (global), with symptoms lasting for 24 hours or more, can cause death without any other cause other than vascular (WHO, 2014 ). The death rate due to stroke is still high. According to estimates from the World Health Organization (WHO) in 2008 there were 6.2 million deaths due to stroke (WHO, 2012). Hemiparese stroke is a post-stroke motor disorder that causes parts of the body to experience weakness. Hemiparesis problems occur due to upper neurons and the weakness is opposite to the side of the brain that is damaged. Muscle strength is closely related to the neuromuscular system that is how much the nervous system's ability to activate the muscles to contract (Maimurahman, 2012). Hemiparese caused by acute stroke causes stiffness, paralysis, weakened muscle strength, and consequently reduces the range of motion of the joints and upper limb function, activities of daily living Activity Daily Living (ADL), such as eating, dressing, and washing (Park, 2007) . Therapy is needed immediately to reduce advanced cerebral injuries, one of the rehabilitation programs that can be given by stroke patients is joint mobilization with ROM. This ROM exercise is done to maintain or improve the level of perfection of the ability to move the joints normally and to increase muscle mass and muscle tone. Results Preliminary studies obtained by researchers with observation techniques of 8 male and 2 female gender patients had decreased Range of Motion ability because they did not undergo physiotherapy routinely.This research is aim to fine related range of motion (ROM) exercise with enhancement ROM ability on post stroke patient who have hemiparese. This research did with correlation description approach with cross sectional design. Sample of this research amount 20 patient. Sampling technique used purposive sampling. Research's instrument consist of questionnaire about exercise range of motion (ROM). Data was analized used chi square test of statistic that is to find corre lation range of motion (ROM) exercise as independent variable and enhancement ability range of motion as depent variable. Research's result showing that is a correlation which significant between range of motion exercise (ROM) with enhancement ability range of motion (P value = 0,001 < 0,005). Range of Motion (ROM) exercise can enhancement ability of range of motion (ROM) in post stroke patient which have hemiparese. This program can applied in nursing physiotherapy asspecially stroke patient and as reference for next research.